The commercialisation of equity - YIP, Man (Institutional Knowledge at Singapore Management University, 2017)
This paper analyses the jurisprudence on the relevance of the commercial context to principles of the law of equity and trusts. We criticise recent UK Supreme Court decisions in the area (chiefly Williams v Central Bank of Nigeria, FHR European Ventures v Cedar Capital Partners and AIB Group v Mark Redler & Co) and identify a trend of the 'commercialisation' of the issues. The cases are placed in comparative context and it is argued that there is an unsatisfactory pattern of judicial reasoning, exhibiting a preference for some degree of unarticulated flexibility in commercial adjudication. But the price of that flexibility is a lack of doctrinal coherence and the development of equitable principles that will apply in, and beyond, the commercial context. We also argue that this trend has important implications for the coming rounds of Supreme Court appointments.